Rapid decline in nuclear costitutive Photomorphogenesis1 abundance anticipates the stabilization of its target elongated Hypocotyl5 in the light - Pacín, Manuel (2014)
In darkness, the E3 ligase COSTITUTIVE PHOTOMORPHOGENESIS1 (COP1) targets to degradation ELONGATED HYPOCOTYL5 (HY5) and other proteins required for photomorphogenesis (Osterlund et al., 2000a; Saijo et al., 2003; Seo et al., 2003). Light inactivates COP1, allowing photomorphogenesis to proceed (Lau and Deng, 2012). Pioneer studies have demonstrated that biologically active COP1-GUS fusion proteins migrate from the nucleus to the cytoplasm (von Arnim and Deng, 1994) but this shift is too slow to be the mechanism of COP1 inactivation involved in rapid lightinduced responses (von Arnim et al., 1997; Lau and Deng, 2012). Here, we re-examine the latter conclusion by using YFP-COP1 and comparing the kinetics to that of nuclear HY5.